Cardiac axis shift within the cardiac cycle of normal fetuses and fetuses with congenital heart defect. (16th October 2015) - Zhao, Y.; Abuhamad, S.; Sinkovskaya, E.; Mlynarczyk, M.; Romary, L.; Abuhamad, A.
Abstract : Linked Comment: Ultrasound Obstet Gynecol 2015; 46: 518–519 ABSTRACT: Objectives: To investigate changes in the cardiac axis (CAx) within the cardiac cycle of normal fetuses and fetuses with congenital heart defects (CHD). Methods: This was a retrospective case–control study in which stored videoclips of four‐chamber views from 527 prenatal ultrasound examinations performed at 18 + 0 to 36 + 6 weeks of gestation were reviewed. Among the ultrasound scans included, 287 were of normal fetuses (controls) and 240 were of fetuses with CHD. In each case, the CAx was measured at end systole (just before the atrioventricular (AV) valve opened) and at end diastole (just before the AV valve closed). CAx measurements of fetuses with CHD were compared to those of controls. Results: The mean CAx in the control group was 45.9 ± 8.5° at end systole and 38.3 ± 8.4° at end diastole ( P < 0.001), resulting in an average difference of 7.6 ± 3.2°. The mean CAx in fetuses with CHD was 53.4 ± 17.8° at end systole and 47.5 ± 17.3° at end diastole ( P < 0.001), resulting in an average difference of 5.9 ± 6.3°. However, in some forms of CHD, such as hypoplastic left heart syndrome and L‐transposition of the great arteries, the CAx was greater at end diastole than at end systole, with a difference of more than 5°. In 21.3% of control fetuses, there was a CAx shift within the cardiac cycle of ≥ 10°. Abnormal CAx measured at end systole was strongly associated with CHD. Conclusions: Measurement of the CAx at end systole provides values that differ from those when measured at end diastole, in both normal fetuses and those with CHD. We recommend that the CAx be measured at end systole as a greater proportion of fetuses with CHD and fewer normal fetuses have an abnormal CAx at this stage compared to at end diastole. The occurrence of an abnormal CAx and the CAx shift within the fetal cardiac cycle depend on the type of CHD. Copyright © 2014 ISUOG. Published by John Wiley & Sons Ltd.